Oceanian Sovereignty in Blue Economy: Ending Unfair Dependency Constraining Small Island Developing States - Farrel Rakha Aryasatya; Falah Mar'ie Amanullah; Mas Intan Putri Apriani; Rahayu Hemalina Prasetyo (Journal of World Trade Studies, 2024)
The implementation of the blue economy in Small Island Developing States (SIDS) can provide a promising economic opportunity to further utilize the riches of marine resources sustainably. Unfortunately, due to the internalized cultural hegemony supporting the economical North-SIDS relations, SIDS still rely upon the investment of the Global North to provide resources to implement this concept. In Neo-Gramscian theory, the Global North is forming a ‘historical bloc’ that uses their resources to maintain an upper hand in their relationship with SIDS. The concept of ‘Oceanian Sovereignty’ in the blue economy acts as a ‘counter-hegemony’ for these countries to unify support for their sovereignty and rights over their own development course through South-South Cooperation. This paper analyzes cases of North-South power imbalance. Using the Neo-Gramscian Theory, this paper uses qualitative methods in analysing the ‘Oceanian Sovereignty’ concept as a gradual effort to counter the Global North domination in the blue economy and look into challenges of the South-South Cooperation to manifest a just transition. This paper finds that under the current state of South-South Cooperation, it is challenging to contest Global North's domination that persists through neoliberal co-optation and economic pressure without sufficient strive for international solidarity and collaboration.